Overexpression of mango alcohol dehydrogenase (MiADH1) mimics hypoxia in transgenic tomato and alters fruit flavor components - Singh, Rajesh Kumar; Srivastava, Smriti; Chidley, Hemangi; Nath, Pravendra; Sane, Vidhu A. (Agri Gene, 2018)
Plant alcohols and aldehydes are produced by the action of alcohol dehydrogenases (ADH) and play an important role during fruit ripening and aroma production. Alcohols are not only produced in different tissues at different stages of plant development but are also products of the fermentative pathway which gets activated by different stresses, including hypoxia. The ADH gene is a well-established marker for hypoxic response as well as plant aroma. In a previous report we have identified and characterized three ADHs (MiADH1, 2, 3) from Dashehari mango. MiADH1 was found to be fruit specific and was upregulated by ethylene and ABA, suggesting a role in fruit aroma volatile production. In order to functionally characterize MiADH1, transgenic tomato plants were developed under the control of the constitutive (CaMV35S) promoter. Transgenic tomato fruit expressing MiADH1 gene showed a change in the levels of several alcohols and aldehydes related to flavor in comparison to the control. The change in aroma and volatiles compounds was more prominent during the ripe stage as compared to unripe and mid-ripe stages of tomato fruit. The transgenic tomato plants also produced adventitious roots. Our results suggest that the overexpression of MiADH1 in tomato plants induced the fermentative pathway in roots, and mimicked hypoxic response by development of adventitious roots from the stem as an adaptive mechanism.